Does the number or the composition of players matter on the mobile broadband markets? - Lessons from a benchmarking study of the largescreen mobile broadband prices in the European Union - Zoltan Papai; Peter Nagy; Bertalan Papp (International Telecommunications Society (ITS), 2017)
Cross-country price comparison is a useful, but often deceptive exercise. The paper addresses the underlying methodological challenges, offering a practicable solution, which is both sound enough and meaningful for the comparison of mobile broadband prices on different markets. Both the simple comparisons and the econometric analysis give valuable insights into how the structural characteristics and also other factors are associated with the price-differences between national mobile markets of the European Union. The result suggests that the presence of a challenger player on the market is important to have lower prices and wider choice of options on the market. This factor seems more important than the mere number of the players.
Keywords: 330